Different traditional Chinese medicine injections combined with conventional therapy for sepsis-induced myocardial dysfunction: a systematic review and network meta-analysis - Deng, Wenjie; Fang, Xiaolei; Huang, Po (Frontiers in Pharmacology, 2026)
ObjectiveAs the use of Traditional Chinese Medicine injections (TCMIs) for sepsis-induced myocardial dysfunction (SIMD) becomes increasingly diverse, this study aims to evaluate their efficacy, optimal combinations, and safety.MethodsA comprehensive computerized search was conducted across multiple databases, including PubMed, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, VIP Database, Wanfang Database, and SinoMed, for randomized controlled trials (RCTs) on TCMIs for treating SIMD, covering the period from the inception of these databases to 25 June 2025. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool (ROB 2.0). A network meta-analysis was performed using Stata 18.0 software. The study protocol has been registered with PROSPERO.ResultsA total of 31 randomized controlled trials (RCTs) were included, comprising 2,166 participants (intervention group: n = 1,099; control group: n = 1,067). Nine TCMIs were investigated: Shenmai injection (SM), Danshen Chuanxiongqin injection (DSCXQ), Xuebijing injection (XBJ), Shenfu injection (SF), Shuxuening injection (SXN), Xinmailong injection (XML), Huangqi injection (HQ), Danhong injection (DH), and Shenqi fuzheng injection (SQFZ). Based on the surface under the cumulative ranking curve values, (1) In reducing 28-day mortality, Shuxuening Injection combined with conventional therapy ranked first based on the Surface Under the Cumulative Ranking Curve (SUCRA) (relative risk [RR], 3.67; 95% confidence interval [CI], 1.09–12.32). (2) For the improvement of cardiac troponin I (cTnI) levels, Danshen Chuanxiongqin Injection combined with conventional therapy ranked first based on SUCRA (mean difference [MD], 0.87; 95% CI, 0.22–1.52). (3) In terms of left ventricular ejection fraction (LVEF) improvement, Shenqi Fuzheng injection combined with conventional therapy ranked first based on SUCRA (MD, −8.79; 95% CI, −15.99 to −1.59). (4) For the reduction of B-type natriuretic peptide (BNP), Xinmailong injection combined with conventional therapy ranked first based on SUCRA (MD, 353.37; 95% CI, 188.55–518.19). (5) Regarding the improvement of N-terminal pro-BNP (NT-proBNP), Danshen Chuanxiongqin injection combined with conventional therapy ranked first based on SUCRA (MD, 557.45; 95% CI, 177.68–937.22). In addition, no significant adverse reactions were reported in the relevant studies on the Shenmai, Danshen Chuanxiongqin, Shenfu, Shuxuening, Huangqi, Danhong and Shenqi fuzheng injections, whereas the Xuebijing and Xinmailong injections demonstrated varying degrees of adverse reactions.ConclusionCompared to conventional therapy alone, the addition of TCMIs in the treatment of SIMD may confer advantages in reducing 28-day mortality, improving levels of cTnI, BNP, and NT-proBNP, as well as increasing LVEF levels. However, due to the low methodological quality of the studies—particularly in blinding and allocation concealment—and poorly documented composition and safety profiles of TCMIs, the reliability of these findings is compromised.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/.